Ferrovias, rede urbana e centralidade urbano-regional: Campina Grande e Mossoró (1907-1929) - Oliveira, Elizângela Justino de (2021)
Cities in the XIX century were marked by intense changes as a result of their population growth and from work field changes brought by the steam engine emergence, but also in the relations between cities promoted by the transport revolution and advances in communication techniques. Those changes directly affected the space-time relation, the urbanization process and the urban civilization somehow and to some degree, considering the inequality of the expansion process of techniques in space. This thesis aims to study the Great Western of Brazil’s railway line from Recife to Limoeiro and Timbaúba (all located in the state of Pernambuco, PE, Brazil) as well as the Campina Grande branch line (in the state of Paraíba, PB, Brazil) and the railway of Mossoró (in the state of Rio Grande do Norte, RN, Brazil). The main objective of this research was to analyze the implications of the implementation of both railways for the restructuring of the urban network of previously referred states and the urban-regional centrality of Campina Grande, PB, and Mossoró, RN, in the period of 1907 to 1929.Thus, the research addresses the Urban Historical Geography according to temporal demarcation and analysis conduction with emphasis on the following primary documental sources: Relatórios dos Presidentes de Províncias e/ou dos Estados do Rio Grande do Norte e da Parahyba, Relatórios do Ministério de Viação e Obras Públicas (1893-1927), Colecção das leis do Império e da República dos Estados Unidos do Brasil (1828-1909), Estatísticas das Estradas de Ferro da União e das fiscalizadas pela União (1904-1930), and Annuarios Estatísticos do Brazil (1908-1912). In addition, the investigative resource of comparison is used, starting from the establishment of criteria, to analyze the hierarchy of cities in the urban network formed by the towns that compose the analyzed railways, such as: the railway forks or bifurcations; the condition of track bumpers; the recipes collected by stations that indicate the present flow density; the political-administrative status of the railway station location (town, village, district or settlement); population attended by each station; architectural imposing of the railway station building. Moreover, the documental analysis established attributes that could verify differences and similarities between both railways, namely: the population benefited by the railway; the number of cities along each of the railways; the transport volume of goods, passengers, baggage and packages, animals and telegrams; if the railway is integrated to a railway network or is an independent railway; if the railway is connected to a port or not; the daily frequency of trains. From the undertaken analysis, one can conclude that the railway implementation in the cities of Campina Grande e Mossoró only resulted in the consolidation of the urban-regional centrality of Campina Grande, as well as the restructuring of the urban network formed by the railway line from Recife to Limoeiro, Timbaúba, and the Campina Grande branch line because of the number of connected cities, attended population, volume of goods, passengers, baggage and telegrams transported.